KECEMASAN, KEPATUHAN DAN KUALITAS HIDUP PASIEN YANG MENJALANI HEMODIALISIS - Emil Huriani; Elvia Donny Harida; Feri Fernandes (Jurnal Keperawatan Muhammadiyah, 2019)
Objective:  to identify anxiety and compliance relationships with quality of life in patients with chronic kidney disease undergoing hemodialysis.Methods:  The research applied cross sectional design with 66 respondents. Analysis of research results using Chi-Square with a degree of significance p≤0,05.Results:  The results showed a significant relationship between anxiety and compliance with patient's quality of life.Conclusion:  It is important to optimize nursing care for anxiety that aims to improve the quality of life of patients with chronic kidney disease.